Minimal retentive sets in tournaments - Brandt, F; Brill, M; Fischer, F; Harrenstein, P (Springer-Verlag, 2013)
Tournament solutions, i.e., functions that associate with each complete and asymmetric relation on a set of alternatives a nonempty subset of the alternatives, play an important role in the mathematical social sciences at large. For any given tournament solution S, there is another tournament solution Ṡ which returns the union of all inclusion-minimal sets that satisfy S-retentiveness, a natural stability criterion with respect to S. Schwartz’s tournament equilibrium set (TEQ) is defined recursively as TEQ = TĖQ. In this article, we study under which circumstances a number of important and desirable properties are inherited from S to Ṡ. We thus obtain a hierarchy of attractive and efficiently computable tournament solutions that “approximate” TEQ, which itself is computationally intractable. We further prove a weaker version of a recently disproved conjecture surrounding TEQ, which establishes ṪC —a refinement of the top cycle — as an interesting new tournament solution.